Kurser och konferenser - Hedlund, Helen (Socialmedicinsk tidskrift, 2019)
The 9th Nordic Health Promotion Research Conference 2019 Health: Societal responsibility or individual obligation? The 12th European Public Health Conference <span style="background: #f1f1f1; color: #333333; font-family: ’Cambria’,serif; font-size: 12pt; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: SV; mso-bidi-language: AR-SA; mso-ascii-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’;" lang="EN-US">"Building bridges for solidarity and public health"